Combined IL-21-primed polyclonal CTL plus CTLA4 blockade controls refractory metastatic melanoma in a patient - Chapuis, Aude G; Lee, Sylvia M; Thompson, John A; Roberts, Ilana M; Margolin, Kim A; Bhatia, Shailender; Sloan, Heather L; Lai, Ivy; Wagener, Felecia; Shibuya, Kendall; Cao, Jianhong; Wolchok, Jedd D; et al. (The Journal of experimental medicine, 2016)
Adoptive transfer of peripheral blood-derived, melanoma-reactive CD8(+) cytotoxic T lymphocytes (CTLs) alone is generally insufficient to eliminate bulky tumors. Similarly, monotherapy with anti-CTLA4 infrequently yields sustained remissions in patients with metastatic melanoma. We postulated that a bolus of enhanced IL-21-primed polyclonal antigen-specific CTL combined with CTLA4 blockade might boost antitumor efficacy. In this first-in-human case study, the combination successfully led to a durable complete remission (CR) in a patient whose disease was refractory to both monoclonal CTL and anti-CTLA4. Long-term persistence and sustained anti-tumor activity of transferred CTL, as well as responses to nontargeted antigens, confirmed mutually beneficial effects of the combined treatment. In this first-in-human study, Chapuis et al. demonstrate that the combination of adoptive cellular therapy with CTLA4 blockade induces long-term remission in a melanoma patient resistant to both modalities administered serially and individually.